Toxicity and Acceptability of Difethialone Baits Against Tatera indica Hardwickei - Choudhary, Vipin; Tripathi, R S (Annals of Arid Zone, 2016)
Indian gerbil, Tatem indica is a predominant vertebrate pest of different production systems of arid ecosystem. It inflicts incalculable losses to crops, grasslands, afforestation sites etc. besides being a carrier of plague bacillus. Three concentrations of difelhialone, viz., 0.00125, 0.0025 and 0.005% were evaluated for three exposure (one, two, three days) under choice and no-choice condition. In no-choice test single day exposure yielded hundred per cent mortality of the test rodents at 0.0025 and 0.005% cone. in 7.90 and 7.10 days, respectively, whereas, increase in feeding period (2 and 3 days) reduced the mean days to death to 4.30 and 5.60 days, respectively. The lowest conc. (0.00125%) yielded 100% mortality after 2 to 3 days exposure with mean days to death 10. I and 10.0 days, respectively. In choice test the i consumption of plain and poison bait was at par for all the three-test concentrations and exposure periods. At ’the lower test concentration (0.00125%), the mortality after I, 2 and 3 days feeding on poison bait was 50, 70 and 90%, however, at 0.0025 and 0.005% concentration, 80% of the test animals succumbed to the anticoagulant in a single day exposure. Thus the present findings proved that difethialone is a fairly palatable and a potent rodenticide for the control of Indian gerbils.